Determinants of the Incidence of Low Birth Weight at the Oesapa Public Health Center, Kupang City in 2020 - Amabi, Stella Sritamar; Aspatria, Utma; Riwu, Rut Rosina (Faculty of Public Health, Nusa Cendana University, 2023)
The level of health in a nation can be determined by the infant and child mortality rate because can describes how big the health problem it is. High infant and child mortality rate is also due to the high incidence of low birth weight. Babies with low birth weight have always been a global health problem, 20 million babies per year 96.5% are born with low weight. This study aims to analyze the determinants of the incidence of low birth weight at the Oesapa Health Center in 2020. Type of this research is a quantitative study with a case control study approach. The study was conducted in the working area of ​​the Oesapa Public Health Center with a sample of 116 mothers, of which 58 mothers with LBW cases and 58 mothers with normal birth weight. The data analysis used was univariabele, bivariabele, and multivariabele analysis with chi square statistical test and multiple logistic regression. The results showed that the factors that influenced the incidence of LBW were age at birth, education level, birth spacing, utilization of ANC examination, consumption pattern with (p= 0.000) and income level (p=0.002) while the factor that had no effect was parity (p= 0.060). Consumption pattern factors (ρ= 0.000), ANC utilization (ρ= 0.001) and education level (p=0.002) were determinant factors for the incidence of LBW. Health centers are expected to be able to utilize various health promotion media in order to increase mother's knowledge of the importance of good consumption patterns and the importance of prenatal care during pregnancy.